2019
DOI: 10.3390/nu11092006
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sociodemographic Factors and Dietary Patterns in Children Under 24 Months of Age: A Systematic Review

Abstract: Background: Understanding early-life complementary feeding dietary patterns and their determining factors could lead to better ways of improving nutrition in early childhood. The purpose of this review was to evaluate evidence of the association between sociodemographic factors and dietary patterns (DPs) in children under 24 months. Methods: Medline (PubMed), Cochrane Central, NICE guidelines, and Trip database were searched for observational studies that evaluated sociodemographic factors and their associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 64 publications
3
19
0
2
Order By: Relevance
“…Four studies did not report any significant dietary intake outcomes. Loss to follow up was a particular concern, especially of participants who are more at risk of providing their infants diets that might be considered of poorer quality 49 . Differences and/or issues in study design, as well as measurement and analysis of dietary outcomes may partially account for these potentially disappointing findings.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies did not report any significant dietary intake outcomes. Loss to follow up was a particular concern, especially of participants who are more at risk of providing their infants diets that might be considered of poorer quality 49 . Differences and/or issues in study design, as well as measurement and analysis of dietary outcomes may partially account for these potentially disappointing findings.…”
Section: Discussionmentioning
confidence: 99%
“…Infant feeding practices were summarized with two complementary approaches: principal component analysis (PCA) and hierarchical ascendant classification (HAC). They represent the two main approaches used in the literature in this topic [ 6 , 10 , 20 , 21 ]. The identification of infant feeding patterns by PCA describes correlations between feeding practices.…”
Section: Methodsmentioning
confidence: 99%
“…The associations between all aspects of feeding during this period have yet to be analyzed in detail. In fact, only few studies have considered the full diet before age 1 year (and none before age 6 months) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could implicate that higher educated mothers may be more healthconscious compared to lower educated mothers, as reported by numerous previous studies 1 9 (e.g. Kant and Graubard, 2013;Ansem et al, 2014;Saldiva et al, 2014;Emmett & Jones, 2015;Durão et al, 2017;Gutiérrez-Camacho et al, 2019;Vilela et al, 2020;Desbouyes et al, 2020). However, from this thesis, this could not be concluded with certainty, because we did not measure health-consciousness as such.…”
Section: Considerations and Value Conflicts In Snack Choicementioning
confidence: 63%
“…Gevers et al (2016) found that 7-12-year-old children of mothers with a lower educational level consumed more energy-dense snacks, compared to children of higher educated mothers. Likewise, studies of Durão et al (2017), Chen et al (2019), van der Velde et al (2019), and Gutiérrez-Camacho et al (2019) confirm the relation between higher maternal education and a healthier dietary pattern of their children. Whether maternal educational attainment influences mothers' snack choices for their 2-7-year-old children and the possible value conflicts experienced is studied in this thesis.…”
Section: Mothers' Educational Levelmentioning
confidence: 79%